Reconstruction of Distal Phalangeal Injuries with Homodigital Island Flap: a Case Report - Atmodiwirjo, Parintosa; Laidding, Sachraswaty (Jurnal Plastik Rekonstruksi, 2012)
Background: Reconstruction of distal phalangeal defects with exposure of bone, tendon, or joint can be a difficult reconstructive problem, particularly since immediate coverage is of paramount importance for preserving function. The objectives of distal phalangeal defect or fingertip reconstruction included preservation of functional length and sensibility, prevention of symptomatic neuromas, acceptable donor site morbidity, the absence of cold intolerance, mineralization of aesthetic deformity, and quick return to occupational activities.Patients and Method: A review of one case, 26 years old male with phalangeal defect at tip to radial site of 3th finger of right hand, with tendon and bone exposed. After adequate debridement, shape and size of the defect are measured, the flap designed at the ulnar site of the same finger and the vascular of the flap is marked to palmar arch. Lazy “S” incision performed, donor flap is elevated with pedicle and transferred to the recipient site. Donor site was covered up with skin graft. Result: After follow up the homo digital island flap was healed nicely and the skin graft take was 100%, length is less diminish, sensibility conformed with two-point description, joint flexibility is good.Summary: Homodigital island flap is a useful safe option for fingertip or distal phalangeal reconstruction because it offers multiple advantages in comparison with advancement, regional, and free flaps, with an almost negligible donor site defect and can be done in a 1-stage procedure.